Swing time [compact disc, unabridged] - Smith, Zadie (Penguin Audio : Books on Tape, 2016)
Two dancers with different approaches to their craft share a complicated childhood friendship that ends abruptly in their early twenties, in a story that transitions from northwest London to West Africa.